2015
DOI: 10.1039/c4tb01294a
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of a hexapeptide hydrogelator for controlled-release drug delivery

Abstract: The amphiphilic peptide sequence H-Phe-Glu-Phe-Gln-Phe-Lys-OH (MBG-1) is developed as a novel hydrogelator for use in controlled-drug release administration, which is the smallest tunable ionic self-complementary hydrogelating peptide reported to date making it attractive for larger scale preparation. Hydrogelation is demonstrated to result from self-assembly of the peptide into beta-sheet nanofibers that are physically cross-linked by intertwining as well as larger bundle formation. Finally, the release of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 31 publications
(39 reference statements)
1
34
0
Order By: Relevance
“…Studies have proven that peptide hydrogels that feature mostly phenylalanine residues have shown higher viscoelastic modulus values. Such higher values are due to the interaction among aromatic-aromatic side-chain amino acids that favor the conversion of the peptides into amyloid-like fibrils, which increases the storage modulus of hydrogels, 13 indicating that secondary structures play a fundamental role in the mechanical properties in this study. In fact, in a previously published work, Besenius and co-workers 10 identified that the conversion of antiparallel to parallel β-sheet structures within the peptide motif attached to PEG termini promotes changes in the mechanical properties of the hydrogel.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Studies have proven that peptide hydrogels that feature mostly phenylalanine residues have shown higher viscoelastic modulus values. Such higher values are due to the interaction among aromatic-aromatic side-chain amino acids that favor the conversion of the peptides into amyloid-like fibrils, which increases the storage modulus of hydrogels, 13 indicating that secondary structures play a fundamental role in the mechanical properties in this study. In fact, in a previously published work, Besenius and co-workers 10 identified that the conversion of antiparallel to parallel β-sheet structures within the peptide motif attached to PEG termini promotes changes in the mechanical properties of the hydrogel.…”
Section: Resultsmentioning
confidence: 82%
“…In Figure 3a, the red line represents the spectrum of compound 1, where we observed two bands, the first one in the position around 1630 cm −1 assigned to antiparallel β-sheets, which can be related to stretching of bonds between adjacent strand layers, 12,22 and the second band around 1661 cm −1 correspondent to TFA counterions. 13 The hybrid hydrogels are depicted by a pronounced band of around 1690 cm −1 , which can be associated to secondary parallel β-sheet structures. However, such band is not present in the neat self-assembled [RF] 4 peptide compound.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels, exciting advanced materials, have drawn much attention owing to their applications in the fields of medicine, nursing care, and sensors . For example, biodegradable hydrogels have significant application as implantable carriers for drug‐delivery systems because of their reliable nontoxicity and high responsiveness . During the past decades, a few notable research studies on the fabrication of biodegradable hydrogels derived either from synthetic materials such as poly(lactic acid), poly(vinyl alcohol), or natural materials such as chitin and gelatin have been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…1 For example, biodegradable hydrogels have significant application as implantable carriers for drugdelivery systems because of their reliable nontoxicity and high responsiveness. 2,3 During the past decades, a few notable research studies on the fabrication of biodegradable hydrogels derived either from synthetic materials such as poly(lactic acid) 4 , poly(vinyl alcohol), 5 or natural materials such as chitin 6 and gelatin 7 have been discussed. In addition, some biodegradable hydrogels have been fabricated from the combination of synthetic and natural materials through interpenetrating polymer networks (IPN) or semi-IPN.…”
Section: Introductionmentioning
confidence: 99%